High efficiency dielectric resonator antenna using complementary ring resonator for bandwidth enhancement - Ghazali, Osman; Khaleel Al-Obaidi, Aymen Dheyaa; Mahmuddin, Massudi; Al Gburi, Ahmed Jamal Abdullah; Mahdi, Mohammed Najah; Mansor, Mohd Fais (Institute of Advanced Engineering and Science, 2022)
A complementary ring resonator (CRR) technique is used to improve the bandwidth of the dielectric resonator antenna (DRA) while maintaining other parameters such as the efficiency and the gain. Parametric experiments were conducted in order to demonstrate the suggested antenna's working guideline. The bandwidth of the proposed Antenna is boosted by 769 percent as compared to the antenna without the CRR technique. The proposed antenna has high efficiency of 94 percent and a tiny dimension of around 30×30×12 mm. The suggested antenna has a frequency range from 2.61 to 3.65 GHz, which is suitable for S-band applications. Computer simulation technology (CST) was used to implement the design and obtain the results.